”Hennes röst blev tonlös när hon började prata svenska”: litterär flerspråkighet och språkväxling - Landqvist, Hans (VAKKI ry, 2012)
In this paper, I present a study of literary multilingualism and literary code switching (‘LCS’) based on Mikael Niemi’s novel Mannen som dog som en lax (2006) [‘The man who died like a salmon']. The novel is set mainly in Tornedalen, a widely bilingual area in Sweden where many people speak both Meänkieli (a recognized minority language, formerly called ‘Tornedal Finnish’) and Swedish. The sender does not consider himself bilingual and most of the intended recipients are not either, even though linguistic conditions are central to the theme of the novel. Swedish is the main language of the novel, while elements of Meänkieli/Finnish and other languages represent a small fraction of the full text. The novel contains examples of LCS used in attempts to reproduce authentic usage and depict an authentic linguistic setting. In other examples, Tornedalen, the Tornedalians, and Meänkieli/Finnish are depicted more as exotic phenomena compared to the majority society.